The decreasing a negative impact of climate change on Indonesian food security - Sulaiman, Andi Amran; Bahrun, Abd. Haris; Husnain, Husnain; Syakir, M.; Amir P, M. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
The negative Impact of climate change and food security are crucial issues for Indonesia with a large population. Agricultural sector as a contributor about 5-7 percent to CO2 emissions, is a victim of climate change as this sector is very sensitive to the change of climate such as rise of temperature, drought, El Nino and La Nina and rise sea level. The decline in production due to climate change and extreme climate is very risky for Indonesia's food security. Various studies and studies have been conducted to evaluate the impact of climate change. However, since 2009, voluntary commitment of Indonesian Government to reduce 26 percent of CO2 emissions set up the strong effort in many sectors to adapt with climate change. In agriculture, improving soil quality is key in maintaining food production. Soil conservation using vegetative or engineering technique is one of the most important technology. Nutrient management by applying balance fertilization, the use of organic material and ameliorant such as biochar, zeolite and other natural mineral are beneficial for plant production. All these ameliorants will be very useful in maintain soil organic matter (SOM) and soil carbon which very important in increasing water holding capacity. Water harvesting is one option to capture high precipitation and important to irrigate agricultural area. Besides, the use of cropping calendars, high yielding varieties which adapt to biophysical stress will be very useful. Other effort is also needed to control the peat fire, peat drainage and deforestation.